Burden of cardiovascular disease from 1990 to 2017 in Henan Province, China - Yan-fang Zhao; Tai Zhang; Zhuo-qun Wang; Xiao-rong Chen; Chun-xiao Wang; Jin-lei Qi; Jing Yang; Jing Wu; Mai-geng Zhou (Taylor & Francis Group, 2021)
Background Cardiovascular diseases (CVDs) are the leading causes of death in China. Little is known about the CVD burden and risk factors in Henan Province, China. Objective To analyze the CVD burden and main risk factors between 1990 and 2017 in the Henan Province in China. Methods The methodological framework and analytical strategies adopted in the Global Burden of Disease Study 2017 were used. Results (1) Age-standardized mortality rate attributed to CVDs increased from 355.0 per 100,000 persons in 1990 to 364.1 per 100,000 persons in 2017 in Henan. (2) Age-standardized disability adjusted life years (DALYs) rate fell by 3.9% from 1990 to 2017. However, the number of DALYs attributed to CVDs increased by 75.9% from 4.2 million person-years in 1990 to 7.3 million person-years in 2017. (3) The age-standardized years lived with disability (YLDs) rate increased by 27.5% from 1990 to 2017. However, years of life lost (YLLs) rate decreased by 6.7% from 1990 to 2017. The contribution of YLLs to the DALYs decreased from 91.4% in 1990 to 89.2% in 2017. (4) Stroke (52.3%) and ischemic heart diseases (38.8%) accounted for 91.1% of total CVDs DALYs among adults in 2017. (5) Dietary factors such as high intake of sodium, alcohol use and low intake of fruits, high systolic blood pressure, and tobacco use were the top risk factors for CVDs, and the estimated population attributable fraction in 2017 was 69.4%, 56.7% and 25.2%, respectively. Conclusions The absolute burden of CVDs in Henan is still high, although age-standardized DALYs declined between 1990 and 2017. The prevention and control of stroke and ischemic heart diseases should focus on a few modifiable risk factors which mainly contributed to the burden of CVDs, such as dietary factors, high systolic blood pressure, and tobacco use.